Search for charged Higgs bosons in e+e- collisions at centre-of-mass energies between 130 and 183 GeV - Dova, María Teresa (1999)
A search for pair-produced charged Higgs bosons is performed with the L3 detector at LEP using data collected at centre-of-mass energies from 130 to 183 GeV, corresponding to an integrated luminosity of 88.3 pb-1 . The Higgs decays into a charm and a strange quark or into a tau lepton and its associated neutrino are considered. The observed candidates are consistent with the expectations from Standard Model background processes. A lower limit of 57.5 GeV on the charged Higgs mass is derived at 95% CL, independent of the decay branching ratio Br(H±→τν).